دراسة وصفية عن حياة السابقين :الخطيب الشربيني وآثاره العلمية / Al-Khatib Syarbiniy and His Scientific Implications: A Descriptive Study of The Life of Classical Scholars - Baso Pallawagau (Diwan : Jurnal Bahasa dan Sastra Arab, 2020)
This study discusses the life of Al-Khatib Syarbiniy, including his biography and scientific footprints to re-review the life of classical scholars. The research problems of this study consist of two questions, including: What is the biography of Al-Khatib Syarbiniy? How is his scientific efforts and footprints? This type of research is qualitative descriptive with several approaches, such as humanist, social, and historical. The data collection method is library research. The results of the study show that: Al-Khatib Syarbiniy lived in the Mamluk and Ottoman era which was characterized by awful politics and difficult social life. However, he did not participate in political life because he was a zuhud man and focused on finding knowledge and teaching it. Al-Khatib Syarbiniy was a figure who was diligent in worship and full of knowledge. His works had fulfilled Arab libraries with various scientific disciplines. The implication of this study is that taking lessons and wisdom from the life of classical scholars, especially the footsteps of Al-Khatib Syarbiniy, reconnecting past and present lives and re-studying turats is a way to improve social society today and in the future.Keywords: Biography, Al-Khatib SyarbiniyAbstrakPenelitian ini membahas tentang kehidupan Al-Khatib Syarbiniy, biografi dan jejak ilmiah beliau untuk mengkaji kembali kehidupan ulama-ulama klasik. Adapun rumusan masalah penelitian ini terdiri dari dua pertanyaan yaitu: Bagaimana biografi Al-Khatib Syarbiniy? Bagaimana upaya dan jejak ilmiah beliau? Jenis penelitian menggunakan deskriptif kualitatif dengan beberapa pendekatan seperti humanis, sosial dan historis. Metode pengumpulan data bersifat penelitian kepustakaan (library research). Hasil penelitian menunjukkan bahwa: Al-Khatib Syarbiniy hidup di era Mamluk dan Ottoman yang memiliki ciri khas perpolitikan yang buruk dan kehidupan sosial yang sulit. Akan tetapi beliau tidak ikutan di dalam kehidupan politik karena beliau sosok lelaki zuhud dan fokus dalam mencari ilmu dan mengajarkannya. Al-Khatib Syarbiniy merupakan sosok yang rajin beribadah dan sarat ilmu pengetahuan, karangan nyamem banjiri perpustakaan Arab dengan berbagai macam disiplin ilmu pengetahuan. Implikasi penelitian ini adalah mengambil pembelajaran dan hikmah dari kehidupan para ulama klasik terlebih khusus jejak Al-Khatib Syarbiniy, menghubungkan kembali kehidupan masa lalu dan masa kini dan kembali mempelajari turats merupakan jalan untuk memperbaiki masyarakat sosial masa kini dan akan datang.